Application of PCR ribotyping and tDNA-PCR for Klebsiella pneumoniae identification - Ana Catarina S Lopes; Juliana Falcão Rodrigues; Maysa BM Clementino; Catia AC Miranda; Ana Paula A Nascimento; Marcos Antônio de Morais Júnior (Memorias do Instituto Oswaldo Cruz, 2007)
PCR analysis of 16S-23S internal transcribed spacer (PCR ribotyping) and tRNA intergenic spacer (tDNA-PCR) were evaluated for their effectiveness in identification of clinical strains of Klebsiella pneumoniae and differentiation with related species. For this purpose both methods were applied to forty-three clinical isolates biochemically identified as K. pneumoniae subsp. pneumoniae isolated from patients clinical specimens attended at five hospitals in three Brazilian cities. References strains of K. pneumoniae subsp. pneumoniae, K. pneumoniae subsp. ozaenae, K. oxytoca, K. planticola and Enterobacter aerogenes were also analyzed. Both PCR methods showed specific patterns for each species. A conserved PCR ribotype pattern was observed for all clinical K. pneumoniae isolates, while differing from other related analyzed species. tDNA-PCR revealed five distinct patterns among the K. pneumoniae clinical isolates studied, demonstrating a predominant group with 90,6% of isolates presenting the same pattern of K. pneumoniae type strain. Both PCR-based methods were not able to differentiate K. pneumoniae subspecies. On the basis of the results obtained, both methods were efficient to differentiate the Klebsiella species analyzed, as well as E. aerogenes. Meanwhile tDNA-PCR revealed different tRNA arrangements in K. pneumoniae, suggesting intra-species heterogeneity of their genome organization, the polymorphism of the intergenic spacers between 16S and 23S rRNA genes appears to be highly conserved whithin K. pneumoniae clinical isolates, showing that PCR ribotyping can be an useful tool for identification of K. pneumoniae isolates.